ANALISIS KESIAPAN SUMBER DAYA PROGRAM STUDI DALAM PENGELOLAAN POLA PEMBELAJARAN BERBASIS PRODUKSI (PRODUCTION BASED EDUCATIO1V): STUDI PADA PROGRAM STUDI D3 AKUNTANSI POLITEKNIK NEGERI SEMARANG (POLINES) - M Noor Ardiansah (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2012)
There has been no clear studies to identib,, venfi, and analyze readiness program resources in order to study the implementation of PBE resulted in initial position (existing point) is not clear that the priority programs and activities that are carried out per year tend to be responsive and not directed priorities. These conditions resulted in analysis of resource readiness courses in the management of production-based learning pattern PBE draw conducted. This study aims to identift and verift and analyze readiness resources management courses in the pattern of production based learning, particularly in the Accounting Studies Program. This research is expected to be used to increase the effectiveness of learning and vocational education to improve the quality and relevance of polytechnic graduates. Total score was 33 the existence of resources from the scale of 12- 60. The average score is 2.75. The average score was shown the position of Prodi's resources have been used, but its role is unclear (repeatable) tend to have clearly defined functions, communicated and documented (defined). Resources have been managed, monitored and evaluated well (managed) are• curriculum resources, networking courses, lab facilities, ISO-based management. Resources have been used but not optimal role: resources module practice, the formulation ofan internship, practice material / TA, the performance ofIC-based lecturer